Case report: Trauma-induced Klebsiella pneumoniae invasive syndrome presenting with liver abscess, lung abscess, endophthalmitis, and purulent meningitis - Hong-qiao Chen; Zhen-hua Mo; Wu-xiao Wei (Frontiers in Medicine)
PurposeThis study aims to explore the underlying causes, diagnostic strategies, and treatment approaches of trauma-induced Klebsiella pneumoniae invasive syndrome (KPIS) through a rare case report. By highlighting the role of trauma as a potential trigger for KPIS, particularly in high-risk populations such as individuals with diabetes, this study seeks to provide valuable insights for improving clinical outcomes and promoting public health awareness.BackgroundKlebsiella pneumoniae invasive syndrome is a multi-organ infectious disease commonly associated with complications such as liver abscess, lung abscess, endophthalmitis, and purulent meningitis, with high mortality and disability rates. In recent years, the incidence of KPIS has been increasing, particularly in the Asia-Pacific region, and is closely linked to hypervirulent Klebsiella pneumoniae (hvKp) infections. While extensive research has focused on the risk of KPIS in patients with underlying conditions such as diabetes, trauma-induced KPIS remains exceedingly rare, with limited understanding of its pathophysiology and clinical management. Trauma may facilitate invasive infections by disrupting immune barriers and compromising local tissue integrity, creating entry points for pathogens.Case presentationThis study reports a case of a 72-year-old male who developed multiple infections, including liver abscess, lung abscess, left endophthalmitis, and purulent meningitis, following a traumatic fall. The patient had a history of poorly controlled diabetes mellitus. A diagnosis of KPIS caused by hvKp was confirmed through bacterial cultures and a positive string test. Imaging studies revealed multi-organ involvement. Given the complexity of the patient’s condition, a comprehensive treatment regimen, including broad-spectrum antibiotics, was implemented with significant therapeutic success. The patient showed marked improvement and continued follow-up after discharge, with a notable resolution of the infections.ConclusionThis case highlights the significance of trauma as a potential trigger for KPIS, particularly in patients with high-risk underlying conditions such as diabetes. Early recognition and the implementation of individualized anti-infective treatment are crucial for reducing mortality and improving prognosis in KPIS patients. Future research should further investigate the relationship between trauma and hvKp infections and develop more comprehensive diagnostic and therapeutic guidelines.